PENGEMBANGAN GAME 2D EDUCATIONAL AND EDUTAINMENT “FRUIT SHOOTER” MENGGUNAKAN UNITY BERBASIS ANDROID - Paryanta - STMIK AUB Surakarta (Indonesian Journal of Networking and Security (IJNS), 2021)
Abstract - The use of Android smartphones by children is generally only for games or playing games that are entertainment. There are many entertainment game developers who do not educate children such as: Clash of Clans, Royal Clash, Angry Bird and many other Android games. Meanwhile, parents have difficulty preventing their children from playing games via smartphones that are less useful and even forget learning time. The purpose of this research is to create an educational and editainment genre game or education based on Android that is useful for kindergarten-elementary level children who like to play Android smartphone games and to introduce local game developers in Indonesia. The system analysis method uses PIECES, while the system development uses the Waterfall method and the system design uses a storyboard. and Unified Modeling Language (UML), namely Use Case Diagrams, Activity Diagrams, Squence Diagrams and Class Diagrams. The game is built using the C # programming language with Unity software. The results of this research have produced a game with a 2D display based on Android. This game is played by 1 person and has 3 levels of obstacles. The genre of this game is educational and edutainment games. Keywords : Android, Smartphone, Game, Educational and Edutainment Abstrak - Pemanfaatan smartphone Android oleh anak-anak umumnya hanya untuk permainan atau main game yang sifatnya sebagai hiburan. Terdapat banyak pengembang game hiburan yang tidak mendidik anak seperti : Clash of Clans, Royal Clash, Angry Bird dan masih banyak Game-Game Android yang lainnya. Sedangkan pihak orangtua mengalami kesulitan untuk mencegah anak-anaknya dalam bermain game melalui smartphone yang kurang bermanfaat dan bahkan sampai lupa waktu belajar. Tujuan dari penelitian ini penulis membuat sebuah game bergenre educational and editainment atau edukasi yang berbasis Android bermanfat untuk anak-anak tingkat TK-SD yang gemar bermain game smartphone Android dan untuk mengenalkan game developer lokal di Indonesia. Metode analisa sistem menggunakan PIECES, sedangkan Pengembangan sistem menggunakan metode Waterfall dan perancangan sistem menggunakan storyboard. dan Unified Modeling Language (UML) yaitu Use Case Diagram, Activity Diagram, Squence Diagram dan Class Diagram. Game dibangun dengan menggunakan bahasa pemrogaman C# dengan sofware Unity. Hasil penilitian ini telah menghasilkan game dengan tampilan 2 Dimensi berbasis Android. Game ini dimainkan oleh 1 orang dan mempunyai 3 level rintangan. Genre dari game ini adalah game educational and edutainment. Kata kunci : Android, Smartphone, Game, Educational and Edutainment